2021
DOI: 10.1111/gcb.15982
|View full text |Cite
|
Sign up to set email alerts
|

Tropical tree growth sensitivity to climate is driven by species intrinsic growth rate and leaf traits

Abstract: A better understanding of how climate affects growth in tree species is essential for improved predictions of forest dynamics under climate change. Long‐term climate averages (mean climate) drive spatial variations in species’ baseline growth rates, whereas deviations from these averages over time (anomalies) can create growth variation around the local baseline. However, the rarity of long‐term tree census data spanning climatic gradients has so far limited our understanding of their respective role, especial… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 116 publications
(145 reference statements)
3
33
1
Order By: Relevance
“…With respect to the field collections, the Australian Wet Tropics in general is characterized by MAP approaching and exceeding 2,000 mm (Turton et al, 1999), a range in which foliar δ 13 C in tropical rainforests is largely insensitive to MAP (Leffler and Enquist, 2002;Diefendorf et al, 2010). In a recent analysis, it was shown that mean climatological water deficit was not a significant predictor of tree growth rates across forests in the Australian Wet Tropics similar to those that we sampled (Bauman et al, 2022a). Furthermore, sap flow measurements at lowland, midelevation, and high elevation sites in the Australian Wet Tropics indicated that transpiration at the tree level is largely unresponsive to seasonal variations in soil moisture (McJannet et al, 2007;Binks et al, 2022).…”
Section: Foliar δ 13 C and Elevationsupporting
confidence: 48%
See 4 more Smart Citations
“…With respect to the field collections, the Australian Wet Tropics in general is characterized by MAP approaching and exceeding 2,000 mm (Turton et al, 1999), a range in which foliar δ 13 C in tropical rainforests is largely insensitive to MAP (Leffler and Enquist, 2002;Diefendorf et al, 2010). In a recent analysis, it was shown that mean climatological water deficit was not a significant predictor of tree growth rates across forests in the Australian Wet Tropics similar to those that we sampled (Bauman et al, 2022a). Furthermore, sap flow measurements at lowland, midelevation, and high elevation sites in the Australian Wet Tropics indicated that transpiration at the tree level is largely unresponsive to seasonal variations in soil moisture (McJannet et al, 2007;Binks et al, 2022).…”
Section: Foliar δ 13 C and Elevationsupporting
confidence: 48%
“…Field campaigns to collect plant functional traits (LMA, foliar δ 13 C and δ 15 N) of exposed canopy branches of focal Flindersia species (a minimum of 2 individuals per site) were conducted in four locations (Supplementary Table 1) across a range in elevation, using standard trait measurement protocols (Cornelissen et al, 2003). Data from a previous trait campaign (Bauman et al, 2022a) were also added to this analysis (n = 16 individuals across five sites for the focal species).…”
Section: Stem Diameter Growth and Plant Functional Trait Measurements...mentioning
confidence: 99%
See 3 more Smart Citations